2012
DOI: 10.1007/s00500-012-0921-6
|View full text |Cite
|
Sign up to set email alerts
|

An optimization algorithm for multimodal functions inspired by collective animal behavior

Abstract: Interest in multimodal function optimization is expanding rapidly since real-world optimization problems often demand locating multiple optima within a search space. This article presents a new multimodal optimization algorithm named as the Collective Animal Behavior (CAB). Animal groups, such as schools of fish, flocks of birds, swarms of locusts and herds of wildebeest, exhibit a variety of behaviors including swarming about a food source, milling around a central location or migrating over large distances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…I tuned the parameter values heuristically for best performance on the objective functions. For the MNC, RCS, and CAB algorithms, I began by using the values from [8], [9], and [12], respectively, but found that modification of some parameters gave better results. The meanings of the variables in Table 4 can be found in [12].…”
Section: Performance Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…I tuned the parameter values heuristically for best performance on the objective functions. For the MNC, RCS, and CAB algorithms, I began by using the values from [8], [9], and [12], respectively, but found that modification of some parameters gave better results. The meanings of the variables in Table 4 can be found in [12].…”
Section: Performance Resultsmentioning
confidence: 99%
“…An approach shown to use even fewer function evaluations is an evolutionary algorithm (EA) by Cuevas and Gonźalez that mimics collective animal behaviour [12]. This algorithm models the way animals are attracted to or repelled from dominant individuals, and retains in memory a set of the fittest individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of PSO. PSO is a population-based metaheuristic algorithm for simulating the predatory activities of bird and fish populations [45,46], and each particle in the population has two properties: velocity vector v i � (v i1 , v i2 , • • • , v id ) and position vector x i � (x i1 , x i2 , • • • , x id ), where d denotes the dimension. In the search process of PSO, the velocity vectors are dynamically adjusted by the personal best position (pbest i ) and the global best position (gbest) at the current stage, and the position vectors are the candidate solutions to the optimization problems, all of which are updated by equations ( 1)- (2).…”
Section: Background and Related Workmentioning
confidence: 99%
“…To examine the proposed MCIA, three evolutionary algorithms HABC (Yan et al 2013), the collective animal behavior, CAB (Cuevas and Gonza'lez 2013), and wolf pack algorithm, WPA (Wu et al 2013) are selected for direct comparisons. Here is a brief description of the three algorithms:…”
Section: Experiments 2: Performance Comparisons Of Mcia With Habc Cabmentioning
confidence: 99%